1988
DOI: 10.1002/gepi.1370050204
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis of juvenile myoclonic epilepsy

Abstract: We examined the inheritance of juvenile myoclonic epilepsy (JME). We looked at both the trait of "epilepsy" and the trait of "epilepsy-plus-EEG abnormalities," since EEG abnormalities are frequently found in the clinically unaffected sibs of JME patients. We tested several modes of inheritance including the fully penetrant recessive and several two-locus models. We could reject all models tested (fully penetrant single-locus and two-locus models) when abnormal EEGs were classified as "unaffected." We could als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Our group originally reported strong linkage of a JME-related gene locus at 6p21, the region containing BRD2. 5 Association analysis pointed to the BRD2 gene as the best-supported candidate. [6][7][8] The JME-6p21 linkage was confirmed multiple times.…”
Section: Introductionmentioning
confidence: 99%
“…Our group originally reported strong linkage of a JME-related gene locus at 6p21, the region containing BRD2. 5 Association analysis pointed to the BRD2 gene as the best-supported candidate. [6][7][8] The JME-6p21 linkage was confirmed multiple times.…”
Section: Introductionmentioning
confidence: 99%
“…Few IGE genes have been identified, and those mostly through linkage scans chosen through specific phenotypes. Of those genes only BRD2 , which is not a channel gene, has been both linked and associated in multiple studies with a particular IGE, JME [5], [6], [7], [8], [9], [10], [11], [12]. The statistical and population evidence supports BRD2 as strongly influencing susceptibility to JME in particular and, potentially, a wider range of IGE syndromes/seizures, including photosensitivity [13], [14] and epilepsy-related electroencephalography (EEG) traits [6], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although IGE is mostly genetic in origin (Greenberg et al 1992), few IGE genes have been identified. Among those genes, BRD2 has been repeatedly both linked and associated with JME (Cavalleri et al 2007;Durner et al 1991;Greenberg et al 1988aGreenberg et al ,1988bGreenberg et al , 2000Pal et al 2003;Sander et al 1995;Weissbecker et al 1991), specifically in Caucasian populations (Greenberg et al 2000;Sander et al 1997).…”
mentioning
confidence: 99%